The Sun's Vertical Depression Effect on True Dawn: A Visual Observation Study - Hariyadi Putraga; Arwin Juli Rakhmadi; Ahmad Abdulwfa (Astroislamica: Journal of Islamic Astronomy, 2026)
This study aims to analyze the influence of the Sun's vertical depth on the appearance of true Dawn in Medan City using the naked-eye observation method. Observations in Medan show that the true dawn light first appears when the Sun is at a depression angle of −14° to −12° below the eastern horizon. The difference between the visible true Dawn and the official dawn time (-20°) is about 6°. These results are consistent with more than 30 studies conducted across over 10 countries at various latitudes, utilizing approximately five different monitoring methods. These results confirm the need to correct the dawn time based on local observations and actual sky conditions, so that the determination of the time of worship better aligns with astronomical reality.